FAKTOR-FAKTOR YANG MEMPENGARUHI INDIA MEMBENTUK ASIA AFRICA GROWTH CORRIDOR (AAGC) - Okso Marisi; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is a political economy study which describes the interests of India in form the Asia Africa Growth Corridor (AAGC). This research will focus on why India form the AAGC, which explained by the factors that drive India to form the AAGC, which is more focused on the African region.This research is qualitative research which used descriptive methods, and collecting datas from some resources like books journals, official publications and relevantwebsites. In this study the author uses Liberalism Perspective and Regional Interest Theory. The object in this research is India an main actor.The result of this research describe the reason India formed AAGC. Factors affecting India to establish AAGC are for India's energy security, Africa's potential for growth is an opportunity for India to increasing cooperation in the health and agriculture sector with Africa, and East African interests as a maritime strategic area for India. Keywords: AAGC (Asia Africa Growth Corridor), Regional Interest Theory, Energy Security, Health and Agriculture Development.